Resource rents, economic growth, and the role of institutional quality: A panel threshold analysis - Abdulahi, Mohamued Elyas; Shu, Yang; Khan, Muhammad Asif (Resources policy, 2019)
This study uses rule of law (i.e., institutional quality; IQ) as a threshold variable and revisits the nonlinear relationship between natural resource rent and economic growth under the resource curse hypothesis. The research utilizes the panel data of 14 resource-rich countries of sub-Saharan Africa (SSA) to identify possible threshold level(s) and to assess the effects using conventional OLS standard error and White-correlated standard error models. The empirical results confirm the existence of two significant threshold effects, indicating a positive relationship between resource rent and economic growth when a country's IQ is above the threshold level of −1.28 and within the range −1.28 to −1.37. However, below the threshold level of −1.37, the resource curse starts to operate, impeding economic growth. The results are robust under the alternative specification of system generalized methods of moment (GMM). Therefore, in contrast to linear and exogenous threshold estimations, this paper shows the required IQ threshold levels for SSA resource-rich countries where they can ensure economic growth using their natural resource windfalls. Failing to account for the endogenous nonlinearities may conceal both the required minimum threshold levels of countries to maintain economic growth and the dynamic effects of IQ. Thus, we recommend policymakers and researchers consider the pivotal role of the threshold effects of IQ to allow for sustainable economic growth. •Asymmetric relationship between resource-rent and economic growth is identified using rule of law as a threshold value.•Two significant threshold levels are identified where resource rents positively affect economic growth.•The threshold effects divided the resource-rich countries into three diffrent regimes.•The disappearance of resource-curse is inferred with a better quality of institutions.